El color de las flores en la taxonomía de cuatro especies de Stanhopea (Orchidaceae) - González L., María Isabel; Mora de Retana, Dora E (Revista de Biología Tropical, 1996)
A statistical study of flower segments color of four Costa Rican orchids: Stanhopea costaricensis, S. gibbosa, S. wardii and S. warscewicziana, showed that the colors of sepals, petals, hipoquile and mesoquile are useful in their identification